Between home and opportunity: Sociocultural factors in rural student perceptions of geographic and socioeconomic mobilities - Bailey, Michelle (Australian and International Journal of Rural Education, 2025)
Much of the academic literature on postsecondary planning for rural students has presented socioeconomic and geographic mobilities as intrinsically linked, arguing that a central dilemma for rural students is whether to stay in their home communities or leave to pursue upward socioeconomic mobility. The present narrative study explores this dilemma from the perspective of two high school juniors from one rural high school in the United States. Though Allen and Gabriella (pseudonyms) attended the same high school, their conceptualisations of their futures were vastly different. Gabriella dreamed of becoming an orthodontist and living in a city. Allen dreamed of owning his own agricultural business and staying in the local community. This article examines each student’s thought process as they chose whether or not to leave their home community. Findings indicate that a combination of sociocultural factors ‘push’ or ‘pull’ students in their respective directions. These factors include students’ lifestyle aspirations, their social identities and relationships with their community, and their views on the role of higher education in financial success. This suggests that rural students’ residential aspirations are more nuanced, individualised, and context-dependent than previously thought.